Synthesis of High-Molecular-Weight Branched Polyethylene Using a Hybrid “Sandwich” Pyridine-Imine Ni(II) Catalyst - Ge, You; Cai, Qi; Wang, Yuyin; Gao, Jiangang; Chi, Yue; Dai, Shengyu (Frontiers in Chemistry, 2022)
Most pyridine-imine Ni(II) and Pd(II) catalysts tend to yield low-molecular-weight polyethylene and ethylene-based copolymers in olefin insertion polymerization, as the unilateral axial steric structure of such complexes often cannot provide effective shielding of the metal center. In this study, we synthesized a series of hybrid “semi-sandwich” and “sandwich” type pyridine-imine Ni(II) complexes by incorporating diarylmethyl or dibenzosuberyl groups onto 8-aryl-naphthyl motif. The as-prepared Ni(II) complexes afforded highly branched polyethylene with high molecular weights (level of 105 g/mol), and moderate activities (level of 105 g/(mol·h)) in ethylene polymerization. Most interestingly, compared to “semi-sandwich” Ni(II) complexes bearing (2-diarylmethyl-8-aryl)naphthyl units, the “full-sandwich” counterpart containing (2-dibenzosuberyl-8-aryl)naphthyl motif was able to produce higher-molecular-weight polyethylene with higher branching density. In addition, the effect of remote non-conjugated electronic substituents in diarylmethyl groups of the Ni(II) system was also observed in ethylene polymerization.